A geopolitics of trauma: Refugee administration and protracted uncertainty in Turkey - Loyd, Jenna M.; Ehrkamp, Patricia; Secor, Anna J. (Transactions - Institute of British Geographers (1965), 2018)
In this paper we map out what we are calling a “geopolitics of trauma” by examining the role of trauma in transnational refugee regimes and the individualisation of geopolitical relations through mental health diagnosis and service provision. Focusing on one site of entry into the international regime of refugee administration, we present findings from fieldwork that we conducted in August, 2015 in Turkey with NGOs and IGOs involved in the protection, mental health and psychosocial service provision, and resettlement of refugees. The findings that we present demonstrate the challenges of refugee care and management on the front lines in Turkey and the significance of mental health diagnosis, treatment and documentation in the early stages of refugee administration. We suggest that practices of refugee screening and resettlement are imbued with traumatic stressors and trace how trauma intersects with the administration of refugees in different sites and at different times. We argue that the protracted situation of refugees in Turkey (many of whom will wait eight years for their Refugee Status Determination interview) and the multiple interviews and demands for documentation through which a displaced person applies for refugee status and third‐country resettlement become sites of ongoing traumatisation for the refugee subject. Further, in the practices of screening and documentation, we can trace the medicalisation of the refugee subject as not only a question of care but also a practice of legibility on which the state and international organisations base their decisions about inclusion and exclusion. The geopolitics of trauma thus emerges not only in cartographies of war, displacement and resettlement, but also in the minute details and performative demands of the refugee determination and resettlement process.